Method for producing wet sheet and molded body of cellulose fiber
A wet sheet made of cellulose fine fibers with controlled moisture and thickness properties addresses the issue of uneven drying and breakage in three-dimensional cellulose fiber molded products, enabling stable and uniform molded articles.
Patent Information
- Application Number
- JP2020200476
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-02
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2040-12-02
AI Technical Summary
Existing methods for producing three-dimensional cellulose fiber molded products face issues with uneven drying and breakage due to non-uniform application of pressure, leading to unstable shapes and handling difficulties.
The use of a wet sheet composed of cellulose fine fibers with specific properties, including a moisture content of 60% by mass or more and a thickness of 0.8 mm to 10 mm, which minimizes deformation and breakage during processing, is achieved by forming a slurry into a sheet and applying controlled pressure.
The method results in a stable, easy-to-handle wet sheet that can be processed into molded articles with uniform thickness and strength, reducing the likelihood of breakage and ensuring homogeneous molded products.
Smart Images

Figure 0007608134000002 
Figure 0007608134000003 
Figure 0007608134000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a wet sheet and a formed article of cellulose fibers. [Background technology]
[0002] In recent years, nanotechnology, which aims to obtain new physical properties different from those of the substance itself by finely pulping a substance to the nano level, has been attracting attention. Nanotechnology has also been applied to cellulose-based raw materials, and cellulose fine fibers obtained by defibrating pulp to the nano level through chemical processing, pulverization, etc., are excellent in strength and elasticity, and are expected to be used for various applications. In particular, molded bodies manufactured by turning cellulose fine fibers into a slurry and drying and molding them have high strength and are a reusable organic resource, so they are useful as versatile materials. For example, Patent Document 1 proposes a "molding method for cellulose nanofibers (CNFs), characterized in that a mold using a vapor permeation means is filled with a slurry containing cellulose nanofibers (CNFs) and a load is applied to the CNF-containing slurry to concentrate it." The document states that "the purpose is to provide a molding method for CNFs that can easily adjust the drying conditions and can stably obtain a CNF molded product with a high level of three-dimensional structure without shrinkage or cracking, and a CNF molded product obtained by the molding method."
[0003] However, when manufacturing a three-dimensional molded body using the method described in the document, if there are areas of different thicknesses when drying the slurry, the load is not applied uniformly, resulting in differences in drying properties at those areas and resulting in breakage. In addition, the slurry has an unstable shape and is not easy to handle. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-94683 A Summary of the Invention [Problem to be solved by the invention]
[0005] The main problem to be solved by the present invention is to provide a wet sheet that is less likely to break during the production of a molded body, has a stable shape, and is easy to handle during processing, and a method for producing a molded body from the wet sheet. [Means for solving the problem]
[0006] Since the slurry contains a large amount of water, it is difficult to determine the shape. In the case of drying this slurry, Patent Document 1 adopts a method of placing the slurry on a porous body, covering the top of the slurry with another porous body, and applying pressure to the slurry with these two porous bodies to crush it and dry it. In this method, when pressure is applied to the slurry in the direction of gravity, a compact with a small thickness difference is formed, but when pressure is applied in a direction other than the direction of gravity, the slurry has a concentration bias due to its own weight, so a compact with a considerable thickness difference is formed. In addition, when a slurry with a concentration bias is dried, breakage occurs due to the difference in shrinkage rate.
[0007] The inventors have conducted extensive research and have come to the conclusion that in order to produce a molded body that is less likely to break, it is preferable to make the raw material for the molded body in a sheet form. In a sheet form, concentration bias like that of a slurry is less likely to occur, and there is almost no difference in the shrinkage rate regardless of the direction in which pressure is applied, making it possible to produce a molded body that is less likely to break. In consideration of the above points, the following is an embodiment of the invention that solves the above problems. (First aspect) The present invention comprises pulp and cellulose fine fibers having an average fiber diameter of 10,000 nm or less, The moisture content is 60% by mass or more and the thickness is 0. 8 mm or more and 10 mm or less. A moist sheet characterized by:
[0008] A wet sheet consisting of only cellulose fine fibers may not be able to provide a molded article with sufficient dehydration. However, if the wet sheet contains pulp and cellulose fine fibers, the molded article will have sufficient dehydration. In addition, since the wet sheet has a tangible form, a moisture content of 60% by mass or more, and a thickness within the above range, it is easily deformed and can be processed into a stable shape. Furthermore, the pulp and cellulose fine fibers in the wet sheet are fixed and do not move freely within the wet sheet as in the case of a slurry. In addition, when a molded article is produced from the wet sheet, the wet sheet is unlikely to break due to the flow of the slurry, and is relatively not bulky, making it easy to handle during processing.
[0009] (Second aspect) The cellulose fine fibers are made of at least one of cellulose nanofibers and microfibrillated cellulose having an average fiber diameter larger than that of the cellulose nanofibers. A wet sheet according to a first embodiment.
[0010] The cellulose fine fibers used in the wet sheet may be cellulose nanofibers, microfibrillated cellulose, or a mixture of cellulose nanofibers and microfibrillated cellulose. In addition, the wet sheet has water retention properties that are insufficient with pulp alone, but since the wet sheet contains at least one of cellulose nanofibers and microfibrillated cellulose, which have excellent water retention properties, the wet sheet has water retention properties.
[0011] (Third aspect) The thickness change rate calculated from the following formula 1 is 0.4 or less. A wet sheet according to the first or second embodiment. [Formula 1] Thickness change rate = ((thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 1 second) - (thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 5 seconds)) ÷ (thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 1 second)
[0012] In addition to the first aspect, since the thickness change rate is 0.4 or less, the wet sheet of this aspect is unlikely to deform in the thickness direction, and thus, when a molded product is produced, breakage due to deformation in the thickness direction is unlikely to occur. Furthermore, since the wet sheet is unlikely to deform in the thickness direction, partial unevenness is unlikely to occur even when pressurized and heated, and a homogeneous molded product can be produced.
[0013] (Fourth aspect) The solid content concentration of the cellulose fine fibers is 10% by mass or more. A wet sheet according to any one of the first to third aspects.
[0014] A molded article containing cellulose fine fibers has a relatively large strength. Since the wet sheet of this embodiment contains the cellulose fine fibers at the above concentration, a molded article having sufficient strength can be produced from the wet sheet.
[0015] (Fifth aspect) A heating and pressurizing step is provided in which the wet sheet is heated and pressed to obtain a molded body, The wet sheet contains pulp and cellulose fine fibers with an average fiber diameter of 10,000 nm or less, has a moisture content of 60% by mass or more, and has a thickness of 0. 8 mm or more and 10 mm or less. The method for producing a molded body comprising the steps of:
[0016] The pulp and cellulose fine fibers are materials that form a wet sheet, and do not move freely like materials that form a slurry. If it is a slurry, the shape of the entire slurry will be deformed by its own weight when processed, but since this embodiment is a wet sheet, the pulp and cellulose fine fibers that form the wet sheet are fixed within the wet sheet, and uneven concentration is unlikely to occur, so breakage is unlikely to occur during processing, and a homogeneous molded product can be produced.
[0017] (Sixth aspect) a preparation step of mixing pulp and cellulose fine fibers having an average fiber diameter of 10,000 nm or less to prepare a slurry; a forming step of sandwiching the slurry between two opposing mesh sheets and applying pressure to dehydrate the slurry to form a wet sheet; A heating and pressurizing step is provided in which the wet sheet is heated and pressed to obtain a molded body, The wet sheet has a moisture content of 60% by mass or more and a thickness of 0. 8 mm or more and 10 mm or less. The method for producing a molded body comprising the steps of:
[0018] In this embodiment, the slurry is processed into a sheet in the processing step to obtain a wet sheet. The wet sheet is in a sheet shape, and is unlikely to change shape due to its own weight, and is unlikely to lose raw materials due to the shedding or loss of part of the pulp or cellulose fine fibers, and is easy to handle.
[0019] (Seventh aspect) The cellulose fine fibers are made of at least one of cellulose nanofibers and microfibrillated cellulose having an average fiber diameter larger than that of the cellulose nanofibers. A method for producing a molded article according to the fifth or sixth aspect.
[0020] This provides the same effects as the second aspect.
[0021] (Eighth aspect) The thickness change rate calculated from the following formula 1 is 0.4 or less. A method for producing a molded article according to any one of the fifth to seventh aspects. [Formula 1] Thickness change rate = ((thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 1 second) - (thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 5 seconds)) ÷ (thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 1 second)
[0022] This provides the same effects as the third aspect.
[0023] (Ninth aspect) The solid content concentration of the cellulose fine fibers is 10% by mass or more. A method for producing a molded article according to any one of the fifth to eighth aspects.
[0024] This provides the same effects as the fourth aspect.
[0025] (Tenth aspect) The forming step is a step carried out without substantial heating. No. 6 A method for producing the molded body according to the embodiment.
[0026] When the moisture is evaporated by heating, the moisture content changes locally in the wet sheet, which may cause uneven moisture content throughout the wet sheet. By not substantially heating the wet sheet, evaporation of moisture is less likely to occur, and uneven concentration of the cellulose fine fibers can be prevented. Effect of the Invention
[0027] According to the present invention, there is provided a wet sheet which is less likely to break during the production of a molded article, has a stable shape, and is easy to handle during processing; and a method for producing a molded article from the wet sheet. [Brief description of the drawings]
[0028] [Figure 1] FIG. 2 is an explanatory diagram of a method for producing a wet sheet. [Diagram 2] FIG. 2 is an explanatory diagram of a method for producing a wet sheet and a molded article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Next, an embodiment of the present invention will be described. Note that the embodiment is an example of the present invention. The scope of the present invention is not limited to the scope of the embodiment.
[0030] The wet sheet of this embodiment has pulp and cellulose fine fibers with an average fiber diameter of 10,000 nm or less, has a moisture content of 60 mass% or more, and a thickness of 0.5 mm or more and 10 mm or less. The cellulose fine fibers are at least one of cellulose nanofibers (hereinafter sometimes referred to as "CNF") and microfibrillated cellulose (hereinafter sometimes referred to as "MFC"), which has an average fiber diameter larger than that of the cellulose nanofibers. The pulp, cellulose nanofibers, microfibrillated cellulose, and wet sheet will be described below.
[0031] (pulp) Pulp is contained in the wet sheet and plays a role of improving the dewatering property of the wet sheet. By adjusting the amount of pulp contained in the wet sheet, the moisture content of the wet sheet can be adjusted to a desired range. In addition, by adjusting the content ratio of pulp and cellulose fine fibers in the wet sheet, the strength of the molded product can be adjusted to a desired range.
[0032] The pulp used in this embodiment can be one or more selected from the raw pulps of cellulose nanofibers described later. In particular, it is preferable to use pulp containing lignin, more preferably mechanical pulp, and particularly preferably BTMP. The use of these pulps further improves the dehydration of the cellulose fiber slurry. It is also preferable to use the pulp used in this embodiment as the same pulp as the cellulose fine fibers. In this way, when the starting materials are the same, the two have a high affinity, and the outflow of the cellulose fine fibers can be suppressed in the process of pressing the slurry to obtain a wet sheet, and dehydration is easily performed and the time required for the process can be shortened.
[0033] The pulp may be unbeaten pulp or beaten pulp. When unbeaten pulp is used, the dewatering efficiency can be increased. When beaten pulp is used, the cellulose fine fibers are easily entangled with the pulp, the outflow of cellulose nanofibers and microfibrillated cellulose can be suppressed, and since there are relatively many hydrogen bonding points, the strength of the obtained molded body can be increased.
[0034] The degree of beating of the pulp can be measured by its freeness, and the freeness of the pulp is, for example, 200 to 800 ml, preferably 350 to 780 ml, and more preferably 400 to 750 ml. If the freeness of the pulp exceeds 800 ml, the wet sheet has improved dewaterability, but is prone to breakage when processed into a molded product or the like, and the fibers become too rigid, preventing integration of the pulp and the cellulose fine fibers, which may result in a failure to improve density.
[0035] On the other hand, if the freeness of the pulp is less than 200 ml, the dewatering ability of the wet sheet may not be improved sufficiently, and the rigidity of the pulp fibers themselves may decrease, causing the wet sheet to be unable to maintain its sheet shape.
[0036] The freeness of pulp is a value measured in accordance with JIS P8121-2 (2012).
[0037] The average fiber diameter of the pulp can be adjusted by selecting the type of pulp and the degree of defibration.
[0038] The average fiber diameter of the pulp (average fiber width; average diameter of a single fiber) is preferably more than 10 to 100 μm, more preferably more than 10 to 80 μm, and particularly preferably more than 10 to 60 μm. If the average fiber diameter of the pulp is within this range, the dewatering property of the wet sheet can be further improved by setting the pulp content within the range described below.
[0039] The average fiber diameter of pulp can be measured by Valmet's fiber analyzer "FS5", which can measure the length and width of cellulose fibers with high accuracy by analyzing the images of diluted cellulose fibers as they pass through the measurement cell inside the fiber analyzer.
[0040] When the average fiber diameters of the pulp and the cellulose fine fibers are within the above-mentioned ranges, the pulp content (solid content concentration) in the wet sheet is preferably 0.1 to 20 mass%, more preferably 0.5 to 12 mass%, and particularly preferably 1.0 to 8 mass%. If the content is less than 0.1 mass%, it may take a long time to dehydrate the wet sheet, which may result in a decrease in productivity. If the content (solid content concentration) exceeds 20 mass%, when a molded product or the like is produced from the wet sheet, the content of the cellulose fine fibers or the like is relatively reduced, so that the strength of the molded product or the like may not be ensured.
[0041] (Cellulose nanofiber) Next, the cellulose nanofibers contained in the wet sheet will be described in detail below. Cellulose nanofibers have many hydrogen bond points of cellulose fibers, and are believed to have the property of dispersing and forming a three-dimensional network structure when mixed with a medium such as water or an organic solvent. This three-dimensional network structure is formed by cellulose nanofibers acting as the skeleton of the three-dimensional network structure, and although it is difficult to describe, it is presumed to have a three-dimensional lattice shape like a jungle gym (however, the three-dimensional lattice may be arranged regularly or irregularly). The inside of the three-dimensional lattice formed by this cellulose nanofiber is void.
[0042] Cellulose nanofibers can be obtained, for example, by defibrating (refining) raw pulp derived from plants. As the raw pulp for cellulose nanofibers, one or more of the following can be selected and used: wood pulp made from broadleaf trees, conifers, etc.; non-wood pulp made from straw, bagasse, cotton, hemp, bast fibers, etc.; waste paper pulp (DIP) made from brown waste paper, envelopes, magazines, flyers, cardboard, white waste paper, imitation waste paper, reclaimed waste paper, recycled waste paper, and broke paper. The above-mentioned various raw materials may be in the form of a pulverized material, such as cellulose-based powder.
[0043] However, in order to prevent impurities from being mixed in as much as possible, it is preferable to use wood pulp. As the wood pulp, for example, one or more types may be selected from chemical pulps such as hardwood kraft pulp (LKP) and softwood kraft pulp (NKP), and mechanical pulp (TMP), etc.
[0044] The hardwood kraft pulp may be bleached hardwood kraft pulp, unbleached hardwood kraft pulp, or semi-bleached hardwood kraft pulp. Similarly, the softwood kraft pulp may be bleached softwood kraft pulp, unbleached softwood kraft pulp, or semi-bleached softwood kraft pulp.
[0045] As the mechanical pulp, for example, one or more types can be selected and used from stone ground pulp (SGP), pressed stone ground pulp (PGW), refiner ground pulp (RGP), chemi-ground pulp (CGP), thermo-ground pulp (TGP), ground pulp (GP), thermo-mechanical pulp (TMP), chemi-thermomechanical pulp (CTMP), refiner mechanical pulp (RMP), bleached thermo-mechanical pulp (BTMP), etc.
[0046] In the production of wet sheets and molded articles, from the viewpoint of the need for high strength, it is preferable to use chemical pulp, and it is more preferable to use LKP and NKP.
[0047] The raw material pulp for the cellulose nanofibers and the raw material pulp for the microfibrillated cellulose may be different from each other, but using the same raw material pulp is preferable because it reduces raw material costs.
[0048] The cellulose nanofibers may be pretreated prior to defibration. For example, the pretreatment may involve mechanically pre-beating the raw pulp or chemically modifying the raw pulp. There are no particular limitations on the method of pre-beating, and known methods can be used.
[0049] Examples of pretreatment of raw material pulp by chemical techniques include hydrolysis of polysaccharides with acids (e.g., sulfuric acid, etc.) (acid treatment), hydrolysis of polysaccharides with enzymes (enzyme treatment), swelling of polysaccharides with alkali (alkali treatment), oxidation of polysaccharides with an oxidizing agent (e.g., ozone, etc.) (oxidation treatment), reduction of polysaccharides with a reducing agent (reduction treatment), oxidation with a TEMPO catalyst (oxidation treatment), anionization (anion treatment) and cationization (cation treatment) by phosphate esterification, carbamate formation, etc.
[0050] When treated with alkali, some of the hydroxyl groups in the hemicellulose and cellulose contained in the pulp are dissociated and the molecules become anionic, weakening the intra- and intermolecular hydrogen bonds, making it easier to defibrate and promoting the dispersion of the cellulose fibers.
[0051] Examples of the alkali used in the alkali treatment include organic alkali such as sodium hydroxide, lithium hydroxide, potassium hydroxide, aqueous ammonia solution, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, and benzyltrimethylammonium hydroxide. From the viewpoint of production costs, it is preferable to use sodium hydroxide.
[0052] By subjecting cellulose nanofibers to enzyme treatment, acid treatment, or oxidation treatment, it is possible to lower the water retention and increase the crystallinity of the cellulose nanofibers, while also increasing the homogeneity of the cellulose nanofibers. In this regard, cellulose nanofibers with low water retention are easier to dehydrate, and the dehydration of the wet sheet is improved.
[0053] When raw pulp is treated with an enzyme, acid, or oxidation, the hemicellulose and amorphous regions of cellulose contained in the pulp are decomposed, and as a result, the energy required for the fine pulp refining process can be reduced, and the uniformity and dispersibility of the cellulose fine fibers can be improved. The dispersibility of cellulose fibers contributes to the homogeneity of molded bodies, for example, when molded bodies are produced from a cellulose fiber slurry. However, since pretreatment reduces the average fiber diameter of the cellulose nanofibers, and as a result, reduces the aspect ratio of the cellulose nanofibers, excessive pretreatment is preferably avoided.
[0054] Examples of cellulose nanofibers that have been modified by anionization to introduce anionic functional groups include cellulose nanofibers that have been esterified with phosphorus oxoacid, cellulose nanofibers that have been carbamate-modified, and cellulose nanofibers in which the hydroxyl groups on the pyranose rings have been directly oxidized to carboxyl groups.
[0055] Cellulose nanofibers modified by the introduction of anionic functional groups have relatively high dispersibility. This is presumably because the anionic functional groups cause localized charge bias, and these anionic functional groups easily form hydrogen bonds with water and organic solvents in the dispersion.
[0056] When cellulose fibers are subjected to esterification with phosphorus oxoacid, which is an example of anionization, the fiber raw material can be finely divided, and the resulting cellulose nanofiber has a large aspect ratio, excellent strength, and high light transmittance and viscosity. Esterification with phosphorus oxoacid can be performed, for example, by the method described in JP 2019-199671 A.
[0057] The esterification reaction with phosphorus oxoacids proceeds by adding a solution of less than pH 3.0 containing an additive containing at least one of phosphorus oxoacids and phosphorus oxoacid metal salts to cellulose fibers and heating.
[0058] Examples of additives include phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, ammonium polyphosphate, lithium dihydrogen phosphate, trilithium phosphate, dilithium hydrogen phosphate, lithium pyrophosphate, lithium polyphosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, sodium polyphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium polyphosphate, phosphorous acid, sodium hydrogen phosphite, ammonium hydrogen phosphite, potassium hydrogen phosphite, sodium dihydrogen phosphite, sodium phosphite, lithium phosphite, potassium phosphite, magnesium phosphite, calcium phosphite, triethyl phosphite, triphenyl phosphite, and phosphorous acid compounds such as pyrophosphorous acid. These additives can be used alone or in combination. However, it is preferable to use phosphonic acids as part or all of the phosphorus oxo acids. The use of phosphonic acids prevents the cellulose fibers from yellowing, and is therefore preferable because it is less likely to affect the color of the molded body.
[0059] Cellulose fibers have a structure in which glucose is one structural unit and multiple glucose units are polymerized. In one polymerized cellulose fiber, the ester group of phosphorus oxoacid may be substituted with a specific glucose and may not be substituted with another glucose. In addition, the ester group of phosphorus oxoacid may be introduced by substitution at multiple positions in a specific glucose.
[0060] Examples of cellulose nanofibers into which cationic functional groups have been introduced by cationic treatment include, but are not limited to, cellulose nanofibers into which groups having cations such as ammonium (e.g., quaternary ammonium), phosphonium, and sulfonium have been introduced.
[0061] An example of a method for introducing a group having a cation is a method in which a reactant and a catalyst are reacted in a solvent to cellulose fibers. The introduction is promoted if the reaction temperature is 10°C or higher and 90°C or lower, and the reaction time is 10 minutes or longer and 10 hours or shorter. Examples of the reactant include glycidyl trimethylammonium chloride, 3-chloro-2-hydroxypropyl trialkylammonium hydride, or halohydrin types thereof. Examples of the catalyst include sodium hydroxide and potassium hydroxide. Examples of the solvent include water or alcohol, and examples of the alcohol include alcohols having 4 or less carbon atoms.
[0062] The reactant is preferably 5% by mass or more, more preferably 10% by mass or more, based on 100% by mass of the cellulose fiber. The catalyst is preferably 0.5% by mass or more, more preferably 1% by mass or more, based on 100% by mass of the cellulose fiber.
[0063] The amount of cationic substituents introduced into the cellulose fibers can be adjusted depending on the reactants, the presence or absence of a catalyst, and the type of solvent. If glucose (e.g., glucopyranose ring) of the cellulose fibers is one constituent unit, it is preferable that 0.01 to 0.4 cationic substituents are introduced per one constituent unit. If the amount is below this range, the effect of introducing the cationic functional group, i.e., the effect of easily defibrating the fibers, is poor. If the amount is above this range, excessive swelling and dissolution of the cellulose nanofibers may occur.
[0064] The cellulose fibers can be defibrated using the following defibration devices and methods. The defibration can be performed by using one or more means selected from homogenizers such as high-pressure homogenizers and high-pressure homogenizers, grinders, grinders, and other mill-type friction machines, refiners such as conical refiners and disk refiners, and various bacteria. However, it is preferable to defibrate the cellulose fibers using a water flow, particularly a high-pressure water flow, and a device or method for finely pulverizing the fibers. This device or method results in very high dimensional uniformity and dispersion uniformity of the resulting cellulose nanofibers. In contrast, for example, when a grinder that grinds between rotating grindstones is used, it is difficult to uniformly finely pulverize the cellulose fibers, and in some cases, there is a risk that some fiber clumps will remain undisintegrated.
[0065] Grinders used to defibrate cellulose fibers include, for example, the Masscolloider manufactured by Masuko Sangyo Co., Ltd. Devices that use high-pressure water flow to pulverize materials include, for example, Starburst (registered trademark) manufactured by Sugino Machine Co., Ltd. and Nanovater (registered trademark) manufactured by Yoshida Kikai Kogyo Co., Ltd. High-speed rotary homogenizers used to defibrate cellulose fibers include the Clearmix-11S manufactured by M Technique Co., Ltd.
[0066] The present inventors have found that when cellulose fibers are defibrated using both a method of grinding between rotating grinding wheels and a method of refining with a high-pressure water jet, and the resulting fibers are observed under a microscope, the fibers obtained using the method of refining with a high-pressure water jet have a more uniform fiber width.
[0067] Defibration using a high-pressure water stream is preferably performed by pressurizing a dispersion of cellulose fibers with a pressure booster to, for example, 30 MPa or more, preferably 100 MPa or more, more preferably 150 MPa or more, and particularly preferably 220 MPa or more (high pressure condition), spraying it from a nozzle with a pore diameter of 50 μm or more, and reducing the pressure so that the pressure difference is, for example, 30 MPa or more, preferably 80 MPa or more, and more preferably 90 MPa or more (reduced pressure condition). The pulp fibers are defibrated by the cleavage phenomenon caused by this pressure difference. If the pressure of the high-pressure condition is low or the pressure difference from the high-pressure condition to the reduced pressure condition is small, the defibration efficiency decreases, and repeated defibration (spraying from the nozzle) becomes necessary to achieve the desired fiber width.
[0068] As a device for defibrating with a high-pressure water flow, it is preferable to use a high-pressure homogenizer. A high-pressure homogenizer is a homogenizer capable of ejecting a slurry of cellulose fibers at a pressure of, for example, 10 MPa or more, preferably 100 MPa or more. When cellulose fibers are treated with a high-pressure homogenizer, collisions between cellulose fibers, pressure differences, microcavitation, etc., occur, and defibration of the cellulose fibers occurs effectively. Therefore, the number of defibration treatments can be reduced, and the production efficiency of cellulose nanofibers can be improved.
[0069] It is preferable to use a high-pressure homogenizer that causes the cellulose fiber slurry to collide in a straight line. Specifically, for example, a high-pressure homogenizer of the counter-collision type (MICROFLUIDIZER (registered trademark), wet jet mill) is used. In this device, two upstream flow paths are formed so that the pressurized cellulose fiber slurry collide in a counter-collision manner at the junction. The cellulose fiber slurry collides at the junction, and the collided cellulose fiber slurry flows out from the downstream flow path. The downstream flow path is provided perpendicular to the upstream flow path, and a T-shaped flow path is formed by the upstream flow path and the downstream flow path. When such a counter-collision type high-pressure homogenizer is used, the energy provided by the high-pressure homogenizer is converted to collision energy to the maximum extent, so that the cellulose fibers can be defibrated more efficiently.
[0070] The cellulose nanofibers obtained by defibration can be dispersed in an aqueous medium to prepare a dispersion liquid prior to mixing with microfibrillated cellulose or pulp. It is particularly preferable that the aqueous medium is entirely water (aqueous dispersion liquid). However, the aqueous medium may be partially other liquids that are compatible with water. As the other liquids, for example, lower alcohols having 3 or less carbon atoms can be used.
[0071] The raw material pulp is preferably defibrated so that the physical properties of the resulting cellulose nanofibers have the desired values or evaluations as shown below.
[0072] <Average fiber diameter> The average fiber diameter of the cellulose nanofibers (average fiber width; average diameter of a single fiber) has a lower limit of 10 nm or more, preferably 15 nm or more, and more preferably 20 nm or more. The upper limit of the average fiber diameter of the cellulose nanofibers is 100 nm or less, preferably 90 nm or less, and more preferably 80 nm or less. If the average fiber diameter of the cellulose nanofibers is less than the lower limit of 10 nm, the dehydration properties of the wet sheet may decrease. If the average fiber diameter of the cellulose nanofibers is the upper limit of 100 nm or less, the cellulose fibers are sufficiently finely refined, and the wet sheet has a dense structure and excellent physical properties.
[0073] The cellulose fine fibers contained in the wet sheet may be only cellulose nanofibers, only microfibrillated cellulose, or both cellulose nanofibers and microfibrillated cellulose. The dehydration property of the cellulose fine fibers is superior in the case of microfibrillated cellulose to that of cellulose nanofibers. By adjusting the blending ratio of the cellulose nanofibers and microfibrillated cellulose, a wet sheet having a desired dehydration property can be obtained. When it is desired to make the dehydration property of the wet sheet relatively high, it is advisable to increase the blending ratio of the microfibrillated cellulose (in this case, the blending ratio of the cellulose nanofibers may be 0), and when it is desired to make the dehydration property relatively low, it is advisable to decrease the blending ratio of the microfibrillated cellulose (in this case, the blending ratio of the microfibrillated cellulose may be 0).
[0074] The average fiber diameter of cellulose nanofibers can be adjusted, for example, by selecting the raw pulp, pre-treating it, defibrating it, etc.
[0075] The method for measuring the average fiber diameter of cellulose nanofibers is as follows. First, 100 ml of an aqueous dispersion of cellulose nanofibers with a solid content concentration of 0.01 to 0.1% by mass is filtered through a Teflon (registered trademark) membrane filter, and the solvent is replaced once with 100 ml of ethanol and three times with 20 ml of t-butanol. Next, the sample is freeze-dried and osmium-coated to obtain a sample. This sample is observed using an electron microscope SEM image at a magnification of 3,000 to 30,000 times depending on the width of the fibers that constitute it. Specifically, two diagonal lines are drawn on the observed image, and three straight lines passing through the intersection of the diagonal lines are arbitrarily drawn. Furthermore, the widths of a total of 100 fibers that intersect with these three straight lines are visually measured. The median diameter of the measured values is then taken as the average fiber diameter.
[0076] <Average fiber length> The average fiber length of the cellulose nanofibers (average length of single fibers) is, for example, 0.3 to 2000 μm, preferably 0.4 to 200 μm, and more preferably 0.5 to 20 μm. If the average fiber length is less than 0.3 μm, the drainage and drying properties may decrease, and a three-dimensional network structure between the cellulose nanofibers may not be easily formed, resulting in a decreased reinforcing effect. If the average fiber length exceeds 2000 μm, the cellulose fibers may become more entangled with each other, making it difficult to form a homogeneous three-dimensional network structure.
[0077] The average fiber length can be adjusted as desired by, for example, selecting the raw pulp, pre-treating, defibrating, and the like.
[0078] The average fiber length of cellulose nanofibers is measured in the same manner as for the average fiber diameter, by visually measuring the length of each fiber. The median length of the measured values is taken as the average fiber length.
[0079] <Aspect ratio> When producing a molded body or the like from a wet sheet, it is preferable to improve the strength while maintaining the ductility of the molded body or the like to a certain extent. From this viewpoint, the aspect ratio of the cellulose nanofibers is preferably such that the lower limit is 3 or more, preferably 6 or more, more preferably 10 or more, and the upper limit is 150,000 or less, preferably 120,000 or less, more preferably 100,000 or less. If the aspect ratio of the cellulose nanofibers is less than 3, the cellulose nanofibers cannot be expected to have fibrous properties. If the aspect ratio of the cellulose nanofibers exceeds 150,000, the viscosity of the prepared cellulose fiber slurry is high, and it may be difficult to produce a wet sheet.
[0080] The aspect ratio is the average fiber length of the cellulose nanofiber divided by the average fiber width of the cellulose nanofiber. The larger the aspect ratio, the more points at which the fibers get caught, which increases the reinforcing effect. However, on the other hand, the more points there are, the lower the ductility of the molded product.
[0081] <Pseudo particle size distribution curve> The peak value in the pseudo particle size distribution curve of the cellulose nanofiber is preferably one peak. When there is one peak, the cellulose nanofiber has high uniformity in fiber length and fiber diameter, and is likely to form a dense three-dimensional structure, and the produced molded article has excellent physical properties. In addition, the cellulose fiber slurry has excellent drying and dehydration properties.
[0082] When the cellulose nanofiber has one peak in the pseudo particle size distribution curve, the smaller the variation (dispersion) in the fiber length and / or fiber diameter of the cellulose nanofiber, the easier it is to form a three-dimensional network structure, which is preferable. When the cellulose nanofiber has one peak in the pseudo particle size distribution curve, the full width at half maximum of the peak is, for example, 250 μm or less, preferably 200 μm or less, and particularly preferably 150 μm. If the full width at half maximum of the peak exceeds 250 μm, the cellulose fibers may not be sufficiently finely divided, and the molded product may not have a dense three-dimensional network structure, which may lead to a decrease in physical properties. To make the full width at half maximum of the peak 250 μm or less, for example, a method such as increasing the number of times of finely dividing treatment can be used.
[0083] The peak value of the cellulose nanofibers may be, for example, 1 μm or more, preferably 3 μm or more, and more preferably 5 μm or more. If the peak value is below 1 μm, the fibers may be excessively defibrated, resulting in a wet sheet or molded product that does not have excellent drainage or drying properties.
[0084] The peak value of the cellulose nanofibers may be, for example, up to 100 μm, preferably up to 80 μm, more preferably up to 60 μm. If the peak value exceeds 100 μm, the fibers may not be sufficiently defibrated, and the uniformity of the fiber diameter and fiber length may be poor.
[0085] The peak value in the pseudo particle size distribution curve of cellulose nanofibers is a value measured in accordance with ISO-13320 (2009). As an example of the measurement, first, a particle size distribution measuring device (a laser diffraction / scattering particle size distribution measuring device from Seishin Enterprise Co., Ltd.) is used to examine the volumetric particle size distribution of an aqueous dispersion of cellulose nanofibers. Next, the median diameter of the cellulose nanofibers is measured from this distribution. This median diameter is taken as the peak value.
[0086] The peak value in the pseudo particle size distribution curve of cellulose nanofibers and the median diameter of the pseudo particle size distribution can be adjusted, for example, by selection of raw material pulp, pretreatment, fibrillation, etc.
[0087] <Pulp viscosity> The pulp viscosity of the fibrillated cellulose nanofibers is preferably 1 cP or more, more preferably 2 cP or more. If the pulp viscosity is less than 1 cP, there is a risk that aggregation of cellulose nanofibers cannot be sufficiently suppressed.
[0088] <Brookfield viscosity> The fibrillated cellulose nanofibers can be mixed with water to form an aqueous dispersion. This cellulose nanofiber aqueous dispersion has viscosity, and this viscosity can be evaluated by Brookfield viscosity. Regarding Brookfield viscosity, even for a dispersion of cellulose nanofibers obtained from a specific raw material by the same manufacturing process, the viscosity varies depending on the concentration of cellulose nanofibers, and the higher the concentration, the higher the viscosity. The Brookfield viscosity of the aqueous dispersion of cellulose nanofibers (solid content concentration 1% (w / w)) is preferably 10 to 4000 cP, more preferably 80 to 3000 cP, and particularly preferably 100 to 2000 cP. An aqueous dispersion with a Brookfield viscosity below 10 cP has poor dispersibility of cellulose nanofibers and may not mix well even when mixed with microfibrillated cellulose or pulp. An aqueous dispersion with a Brookfield viscosity exceeding 4000 cP results in poor dewaterability of the slurry or wet sheet obtained by mixing this aqueous dispersion with microfibrillated cellulose or pulp.
[0089] The Brookfield viscosity of the dispersion of cellulose nanofibers (solid content concentration 1% (w / w)) is a value measured in accordance with "Method for Measuring Viscosity of Liquids" of JIS-Z8803 (2011). Brookfield viscosity is the resistance torque when the dispersion is stirred, which means that the higher the value, the more energy is required for stirring. The measurement temperature of Brookfield viscosity is 25°C.
[0090] <Crystallinity> The crystallinity of the cellulose nanofiber is preferably 50% or more, more preferably 55% or more, and particularly preferably 60% or more. If the crystallinity is less than 50%, the strength and heat resistance of the molded article may be insufficient.
[0091] On the other hand, the crystallinity of the cellulose nanofiber is preferably 100% or less, more preferably 90% or less, and particularly preferably 85% or less. If the crystallinity of the cellulose nanofiber is within the above range, strength is ensured during the process of producing a wet sheet, a molded product, or the like from the cellulose fiber slurry.
[0092] The degree of crystallinity of cellulose nanofibers can be adjusted as desired, for example, by selecting the raw pulp, pre-treating it, and refining it.
[0093] The degree of crystallinity is a value measured by X-ray diffraction in accordance with JIS-K0131 (1996) "General Rules for X-ray Diffraction Analysis." Note that cellulose nanofibers have amorphous and crystalline parts, and the degree of crystallinity refers to the proportion of crystalline parts in the entire cellulose nanofiber.
[0094] <Water retention> The water retention of the cellulose nanofiber is, for example, 90 to 600%, preferably 200 to 500%, and more preferably 240 to 460%. If the water retention of the cellulose nanofiber is less than 90%, dispersibility may deteriorate, and the cellulose nanofiber, microfibrillated cellulose, and pulp may not be mixed with each other. If the water retention exceeds 600%, the prepared slurry may have poor drainage and drying properties.
[0095] The water retention of cellulose nanofibers can be adjusted as desired, for example, by selecting the raw pulp, pre-treating it, defibrating it, etc.
[0096] The water retention of cellulose nanofiber is a value measured in accordance with JAPAN TAPPI No. 26 (2000).
[0097] The content (solid content) of cellulose nanofibers in the wet sheet is, for example, 0 to 39.6% by mass, preferably 10 to 38% by mass, and more preferably 12 to 36% by mass. This content range is preferable because the cellulose nanofibers are appropriately dispersed in the wet sheet. In addition, even when a molded product or the like is produced from the wet sheet, the cellulose nanofibers are preferably appropriately dispersed in the molded product or the like. If the content exceeds 39.6% by mass, the drainage and drying properties are not good.
[0098] (Microfibrillated cellulose) Next, the microfibrillated cellulose contained in the wet sheet will be described in detail below. Microfibrillated cellulose has many hydrogen bond points of cellulose fibers, has dehydrating properties, and disperses when mixed with a medium such as water or an organic solvent. Microfibrillated cellulose can be produced by defibrating raw pulp, and is a fiber with an average fiber diameter larger than that of cellulose nanofibers.
[0099] Microfibrillated cellulose can be obtained, for example, by defibrating (refining) raw pulp derived from plants. As the raw pulp for microfibrillated cellulose, one or more of the following can be selected and used: wood pulp made from broadleaf trees, conifers, etc.; non-wood pulp made from straw, bagasse, cotton, hemp, bast fiber, etc.; waste paper pulp (DIP) made from brown waste paper, envelope paper, magazine paper, flyer paper, cardboard paper, white waste paper, imitation waste paper, reclaimed waste paper, recycled waste paper, and broke paper. The above-mentioned various raw materials may be in the form of a pulverized material, such as cellulose-based powder.
[0100] However, in order to prevent impurities from being mixed in as much as possible, it is preferable to use wood pulp. As the wood pulp, for example, one or more types may be selected from chemical pulps such as hardwood kraft pulp (LKP) and softwood kraft pulp (NKP), and mechanical pulp (TMP), etc.
[0101] The hardwood kraft pulp may be bleached hardwood kraft pulp, unbleached hardwood kraft pulp, or semi-bleached hardwood kraft pulp. Similarly, the softwood kraft pulp may be bleached softwood kraft pulp, unbleached softwood kraft pulp, or semi-bleached softwood kraft pulp.
[0102] As the mechanical pulp, for example, one or more types can be selected and used from stone ground pulp (SGP), pressed stone ground pulp (PGW), refiner ground pulp (RGP), chemi-ground pulp (CGP), thermo-ground pulp (TGP), ground pulp (GP), thermo-mechanical pulp (TMP), chemi-thermomechanical pulp (CTMP), refiner mechanical pulp (RMP), bleached thermo-mechanical pulp (BTMP), etc.
[0103] In the production of wet sheets and molded articles, from the viewpoint of the need for high strength, it is preferable to use chemical pulp, and it is more preferable to use LKP and NKP.
[0104] The method for defibrating raw pulp into microfibrillated cellulose can be the same as the method for defibrating cellulose nanofibers described above. However, defibrating into microfibrillated cellulose does not result in a smaller average fiber diameter than defibrating into cellulose nanofibers.
[0105] The microfibrillated cellulose obtained by defibration can be dispersed in an aqueous medium to prepare a dispersion liquid prior to mixing with cellulose nanofibers or pulp. It is particularly preferable that the aqueous medium is entirely water (aqueous dispersion liquid). However, the aqueous medium may be partially other liquids that are compatible with water. As the other liquids, for example, lower alcohols having 3 or less carbon atoms can be used.
[0106] The raw material pulp is preferably defibrated so that the physical properties of the resulting microfibrillated cellulose have the desired values or evaluations as shown below. The methods for measuring the various physical properties of the microfibrillated cellulose are the same as those for cellulose nanofibers and pulp, unless otherwise specified.
[0107] <Average fiber diameter> The average fiber diameter of microfibrillated cellulose (average fiber width; average diameter of single fiber) is more than 100 nm, preferably 200 nm or more, more preferably 300 nm or more. The upper limit of the average fiber diameter of microfibrillated cellulose is 10,000 nm or less, preferably 5,000 nm or less, more preferably 3,000 nm or less. If the average fiber diameter of microfibrillated cellulose is 100 nm or less, the dehydration of the wet sheet may decrease and it may become difficult to distinguish from cellulose nanofibers, so this should be avoided. If the average fiber diameter of microfibrillated cellulose exceeds the upper limit of 10,000 nm, the cellulose fibers may not be sufficiently fine.
[0108] The average fiber diameter of the microfibrillated cellulose can be adjusted, for example, by the selection of raw pulp, pretreatment, defibration, etc.
[0109] The average fiber diameter of microfibrillated cellulose is measured as follows. First, 100 ml of an aqueous dispersion of microfibrillated cellulose with a solid content concentration of 0.01 to 0.1% by mass is filtered through a Teflon (registered trademark) membrane filter, and the solvent is replaced once with 100 ml of ethanol and three times with 20 ml of t-butanol. Next, the sample is freeze-dried and osmium-coated to obtain a sample. This sample is observed using an electron microscope SEM image at a magnification of 3,000 to 30,000 times depending on the width of the fibers that constitute it. Specifically, two diagonal lines are drawn on the observed image, and three straight lines passing through the intersections of the diagonal lines are arbitrarily drawn. Furthermore, the widths of a total of 100 fibers that intersect with these three straight lines are visually measured. The median diameter of the measured values is then taken as the average fiber diameter.
[0110] <Average fiber length> The average fiber length of the microfibrillated cellulose (average length of a single fiber) is, for example, 10 to 1000 μm, preferably 30 to 700 μm, and more preferably 50 to 500 μm. If the average fiber length is less than 30 μm, the drainage and drying properties may decrease, and the reinforcing effect of the produced wet sheet, molded product, etc. may decrease. If the average fiber length exceeds 1000 μm, the cellulose fibers become more entangled with each other, and dispersibility decreases.
[0111] The average fiber length can be adjusted as desired by, for example, selecting the raw pulp, pre-treating, defibrating, and the like.
[0112] The average fiber length of microfibrillated cellulose is measured in the same manner as in the case of the average fiber diameter, by visually measuring the length of each fiber. The median length of the measured values is taken as the average fiber length.
[0113] <Aspect ratio> When producing a molded article or the like from a wet sheet, it is preferable to improve the strength of the molded article or the like while maintaining the ductility of the molded article or the like to a certain extent. From this viewpoint, the aspect ratio of the microfibrillated cellulose has a lower limit of 3 or more, preferably 5 or more, more preferably 10 or more, and an upper limit of 10,000 or less, preferably 7,000 or less, more preferably 5,000 or less. If the aspect ratio of the microfibrillated cellulose is less than 3, the microfibrillated cellulose cannot be expected to have fibrous properties. If the aspect ratio of the microfibrillated cellulose exceeds 10,000, the viscosity of the prepared cellulose fiber slurry is high, and it may be difficult to produce a wet sheet.
[0114] The aspect ratio is the value obtained by dividing the average fiber length of the microfibrillated cellulose by the average fiber width of the microfibrillated cellulose. The larger the aspect ratio, the more points at which the fibers are caught, and therefore the greater the reinforcing effect. On the other hand, it is considered that the greater the number of points at which the fibers are caught, the lower the ductility of the molded product, etc.
[0115] <Pseudo particle size distribution curve> The peak value in the pseudo particle size distribution curve of the microfibrillated cellulose is preferably one peak. When there is one peak, the microfibrillated cellulose has high uniformity in fiber length and fiber diameter, and is likely to form a dense three-dimensional structure, and the produced molded article has excellent physical properties. In addition, the cellulose fiber slurry has excellent drying and dehydration properties.
[0116] When the microfibrillated cellulose has one peak in the pseudo particle size distribution curve, the smaller the variation (dispersion) of the fiber length and / or fiber diameter of the microfibrillated cellulose, the easier it is to form a three-dimensional network structure, which is preferable. When the microfibrillated cellulose has one peak in the pseudo particle size distribution curve, the full width at half maximum of the peak is, for example, 250 μm or less, preferably 200 μm or less, and particularly preferably 150 μm. If the full width at half maximum of the peak exceeds 250 μm, the cellulose fibers may not be sufficiently fined, and the molded product may not have a dense three-dimensional network structure, which may lead to a deterioration in physical properties. To make the full width at half maximum of the peak 150 μm or less, for example, a method such as increasing the number of times of fine processing can be used.
[0117] The peak value of the microfibrillated cellulose may have a lower limit of, for example, 1 μm or more, preferably 5 μm or more, and more preferably 10 μm or more. If the peak value is below 1 μm, the fibers may be excessively defibrated, resulting in a wet sheet or molded product that is inferior in drainage and drying properties.
[0118] The peak value of the microfibrillated cellulose may be, for example, up to 110 μm, preferably up to 100 μm, more preferably up to 90 μm. If the peak value exceeds 110 μm, the fibers may not be sufficiently defibrated, and the uniformity of the fiber diameter and fiber length may be poor.
[0119] The peak value in the pseudo particle size distribution curve of microfibrillated cellulose is a value measured in accordance with ISO-13320 (2009). As an example of the measurement, first, a particle size distribution measuring device (a laser diffraction / scattering type particle size distribution measuring device manufactured by Seishin Enterprise Co., Ltd.) is used to examine the volumetric particle size distribution of an aqueous dispersion of microfibrillated cellulose. Next, the median diameter of the microfibrillated cellulose is measured from this distribution. This median diameter is taken as the peak value.
[0120] The peak value in the pseudo-particle size distribution curve of the microfibrillated cellulose and the median diameter in the pseudo-particle size distribution can be adjusted, for example, by the selection of raw pulp, pretreatment, defibration, etc.
[0121] <Pulp viscosity> The pulp viscosity of the defibrated microfibrillated cellulose is preferably 1 cP or more, and more preferably 2 cP or more. If the pulp viscosity is less than 1 cP, aggregation of the microfibrillated cellulose may not be sufficiently suppressed.
[0122] <Crystallization degree> The crystallinity of the microfibrillated cellulose is preferably 45% or more, more preferably 55% or more, and particularly preferably 60% or more. If the crystallinity is less than 45%, the strength and heat resistance of the molded article may be insufficient.
[0123] On the other hand, the crystallinity of the microfibrillated cellulose is preferably 90% or less, more preferably 88% or less, and particularly preferably 86% or less. When the crystallinity of the microfibrillated cellulose is within the above range, strength is ensured in the process of producing a wet sheet, a molded product, etc. from the cellulose fiber slurry.
[0124] The crystallinity of the microfibrillated cellulose can be adjusted as desired, for example, by selecting the raw pulp, pre-treating it, and refining it.
[0125] The crystallinity is a value measured by X-ray diffraction in accordance with JIS-K0131 (1996) "General Rules for X-ray Diffraction Analysis." Note that microfibrillated cellulose has an amorphous portion and a crystalline portion, and the crystallinity refers to the proportion of the crystalline portion in the entire microfibrillated cellulose.
[0126] <Water retention> The water retention of the microfibrillated cellulose is, for example, 10 to 500%, preferably 50 to 450%, and more preferably 90 to 400%. If the water retention of the microfibrillated cellulose is less than 10%, dispersibility may deteriorate, and the microfibrillated cellulose, cellulose nanofibers, and pulp may not be mixed with each other. If the water retention exceeds 500%, the prepared slurry may have poor drainage and drying properties.
[0127] The water retention of microfibrillated cellulose can be adjusted as desired, for example, by selecting the raw pulp, pre-treating it, defibrating it, etc.
[0128] The water retention of microfibrillated cellulose is a value measured in accordance with JAPAN TAPPI No. 26 (2000).
[0129] The fibrillation rate of the microfibrillated cellulose is preferably 0.5% or more, more preferably 1.0% or more, and particularly preferably 1.5% or more. The fibrillation rate is preferably 10% or less, more preferably 9% or less, and particularly preferably 8% or less. If the fibrillation rate exceeds 10%, the contact area with water becomes too large, which may make dehydration difficult. On the other hand, if the fibrillation rate is less than 0.5%, there is a risk that the hydrogen bonds between the fibrils are small and a strong three-dimensional network structure cannot be formed.
[0130] The freeness of the microfibrillated cellulose is preferably 200 ml or less, more preferably 150 ml or less, and particularly preferably 100 ml or less. If the freeness of the microfibrillated cellulose exceeds 200 ml, the microfibrillated cellulose exceeds the upper limit of the average fiber diameter of 10 μm, and there is a risk that the effect regarding strength cannot be sufficiently obtained.
[0131] The freeness of the microfibrillated cellulose is a value measured in accordance with JIS P8121-2 (2012).
[0132] <Mixing ratio> The content (solid content) of microfibrillated cellulose in the wet sheet is, for example, 0 to 39.6% by mass, preferably 10 to 38% by mass, and more preferably 12 to 36% by mass. This content range is preferable because the microfibrillated cellulose is appropriately dispersed in the wet sheet. In addition, when a molded product or the like is produced from the wet sheet, the microfibrillated cellulose is preferably appropriately dispersed in the molded product or the like. If the content exceeds 39.6% by mass, the freeness and drying properties are not good.
[0133] (Wet Sheet) The wet sheet is produced from a cellulose fiber slurry in which at least one of cellulose nanofibers and microfibrillated cellulose is mixed with pulp. The method for producing the wet sheet will be described later.
[0134] Conventional CNF molded bodies disclosed in Japanese Patent Application Publication No. 2017-190529 and the like are in the form of a flat sheet. The following problems exist in deforming this CNF molded body into a molded body of a desired three-dimensional shape. Since it is difficult to deform the CNF molded body into a three-dimensional shape in a dry state, a method has been used in which the CNF molded body is softened by impregnating it with water and then deformed in the softened state. This method requires the addition of a step of drying the deformed CNF molded body again, which leads to a decrease in productivity and an increase in manufacturing costs.
[0135] In contrast, the wet sheet of the present embodiment is tangible but easily deformable, can temporarily maintain a desired shape, and is useful as a material for shaped articles of various three-dimensional shapes. Various physical properties of the wet sheet are shown below.
[0136] The moisture content of the wet sheet is preferably 60% by mass or more, more preferably 63% by mass or more, and even more preferably 65% by mass or more. If the moisture content is less than 60% by mass, the flexibility of the wet sheet decreases, and it becomes difficult to mold the molded product into a desired shape. The upper limit of the moisture content is not particularly limited, but if it is 90% by mass or less, it is preferable because the uneven thickness that tends to occur in the molded product during production is suppressed and the molded product has uniform strength.
[0137] The moisture content of the wet sheet can be measured according to JIS P 8203 (2010).
[0138] The thickness of the wet sheet is preferably 0.5 mm or more, more preferably 0.8 mm or more, and even more preferably 1 mm or more, and is preferably 10 mm or less, more preferably 9 mm or less, and even more preferably 8 mm or less. If the thickness of the wet sheet is less than 0.5 mm, the wet sheet is easily torn. If the thickness of the wet sheet is more than 10 mm, the molded product produced by pressing and heating is likely to have uneven thickness.
[0139] In addition, it is desirable for the wet sheet to have a thickness of 0.5 mm or more and 10 mm or less and a moisture content of 60 mass % or more. Even if the thickness is 0.5 mm or more and 10 mm or less, if the moisture content is below 60 mass %, it becomes difficult to bend or fold the wet sheet, making it difficult to form a molded body into a three-dimensional shape.
[0140] The thickness of the wet sheet can be measured according to JIS P 8118 (2014).
[0141] The thickness change rate indicates the degree of compressibility of a wet sheet in the thickness direction, and the lower the value, the less compressible it is, and when the wet sheet is heated and pressurized to form a molded product, the thickness will be less uneven and the product will be less likely to break.The higher the thickness change rate, the more easily the wet sheet is compressed and the more easily it deforms when heated and pressurized, and the more likely the molded product will break.
[0142] The thickness change rate can be calculated based on the following formula (1). [Formula (1)] Thickness change rate = ((thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 1 second) - (thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 5 seconds)) ÷ (thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 1 second)
[0143] The thickness change rate can be appropriately adjusted, but is preferably 0.4 or less, more preferably 0.35 or less, and even more preferably 0.3 or less, so that unevenness in thickness is reduced and the film is less likely to break.
[0144] The thickness change rate can be measured as follows. Both sides of a wet sheet are entirely covered with a film, a pressure of 100 kPa is applied in the thickness direction for 1 second, and the thickness of the wet sheet is measured. Further, a pressure of 100 kPa is applied in the thickness direction for 5 seconds, and the thickness of the wet sheet is measured. The measurement can be performed under atmospheric pressure and room temperature (5 to 30°C, particularly 25°C, 1 atm).
[0145] <Mixing ratio> The blending ratio of the pulp and cellulose fine fibers contained in the wet sheet is, for example, 1:99 to 50:50, preferably 5:95 to 30:70, and more preferably 10:90 to 20:80.The blending ratio of the cellulose nanofibers and microfibrillated cellulose is, for example, 100:0 to 0:100, preferably 80:20 to 20:80, and more preferably 70:30 to 30:70.
[0146] <Water retention> The wet sheet preferably has a water retention of 250 to 4000 g / m when the wet sheet is dispersed in an aqueous medium to prepare a dispersion having a concentration of 1.5%. 2 , more preferably 500 to 3000 g / m 2 The water retention is 250g / m 2 If it is less than 4000g / m, it has poor wettability. 2 If the temperature exceeds this range, the wet sheet may not be able to maintain its shape.
[0147] <density> The wet sheet is dehydrated and dried under conditions of 1 to 50 MPa and 100 to 150°C to increase density, and when formed into a molded product, the density is preferably 0.8 to 1.5 g / m 3 , more preferably 0.9 to 1.4 g / m 3 , and particularly preferably 1.0 to 1.3 g / m 3 The density is 0.8g / m 3 If the density falls below 1.5 g / m, the molded product will be easily broken during molding. 3 If the content exceeds this range, it may become difficult to handle during processing.
[0148] The wet sheet may contain cellulose fine fibers in an amount exceeding 0% by mass in terms of solid content, but preferably contains 10% by mass or more, more preferably 11% by mass or more, and even more preferably 12% by mass or more, so that the strength of the molded product is increased. The upper limit of the cellulose fine fibers contained in the wet sheet is not particularly limited, but since pulp is also contained, the solid content may be, for example, preferably 39.6% by mass or less, more preferably 38% by mass or less.
[0149] (Wet Sheet Manufacturing Method) Next, a method for producing the wet sheet and the formed product will be described. The method comprises a preparation step 10 for preparing a slurry, a formation step 20 for forming a wet sheet, and a heating and pressurizing step 30 for heating and pressurizing the wet sheet. These steps will be described in order.
[0150] (Preparation process) In the slurry preparation step 10, as shown in FIG. 2, pulp P and cellulose fine fibers (cellulose nanofibers C and / or microfibrillated cellulose M) are mixed with an aqueous medium W to prepare a slurry S.
[0151] The solid content of the cellulose fibers contained in the slurry (i.e., the total amount of the pulp P and the cellulose fine fibers) is preferably 1.0 to 10.0 mass%, more preferably 1.2 to 7.0 mass%, and particularly preferably 1.4 to 5.0 mass%. If the solid content of the cellulose fibers is less than 1.0 mass%, the fluidity is high and there is a high possibility that the cellulose fibers will flow out in the subsequent forming step 20.
[0152] On the other hand, if the solids concentration of the cellulose fibers contained in the slurry (i.e., the total amount of pulp P and cellulose fine fibers) exceeds 10.0 mass %, the fluidity will decrease significantly and processability will deteriorate, so that, for example, uneven thickness will be likely to occur in the process of producing a wet sheet, making it difficult to obtain a homogeneous wet sheet.
[0153] The medium (aqueous medium) W such as water is preferably entirely water. However, the aqueous medium W may be partially other liquids that are compatible with water. As the other liquids, for example, lower alcohols having 3 or less carbon atoms and ketones having 5 or less carbon atoms can be used.
[0154] The cellulose fiber slurry can have a water retention capacity of 250 to 4000 g / m by adjusting the pulp content appropriately. 2 It is preferable to set the thickness to 500 to 3000 g / m 2 The higher the water retention, the easier it is to dehydrate the slurry. 2 If the water retention exceeds 250 g / m, the dispersibility decreases and it is difficult to produce a homogeneous molded product. 2 If the temperature is lower than this, the dehydration step will not be sufficient or will require a long time for dehydration, resulting in a decrease in productivity.
[0155] The water retention of the cellulose fiber slurry was measured in accordance with TAPPI T 701 pm-01 (2001). The measurement procedure was as follows: (1) A PCTE filter was placed on top of a filter paper for measuring water retention (the dry weight of which had been measured beforehand). (2) The above-mentioned (1) was clamped in a special tool, and the measurement sample (slurry) was added. (3) Measurement (processing) was performed under the measurement conditions described below. (4) The PCTE filter was removed from the filter paper, and the weight of the filter paper was measured. (5) The water retention was calculated using the following formula (2). The measurement conditions were as follows: A cellulose fiber slurry (concentration 1.5% by mass, temperature 30°C) was added to a water retention measuring device AA-GWR (manufactured by Kaltec Scientific), and an air pressure of 1.5 kgf / cm was applied. 2 The measurement time was 30 seconds. [Formula (2)] Water retention (g / m 2 ) = (filter paper weight after dehydration - filter paper dry weight) x 1250
[0156] (Formation process) In the forming step 20, the prepared cellulose fiber slurry is sandwiched between two opposing reticulate sheets and pressurized to dehydrate the slurry, forming the slurry into a wet sheet. In the forming step 20, referring to FIG. 1, reticulate sheets 12 are layered from the bottom inside a cylindrical form 13 placed on a table, and slurry 11 is filled on top of the reticulate sheets 12. The filled slurry 11 is covered from above with a reticulate sheet 14. If the form 13 is made of a porous material, dehydration is promoted, and the time required for the wet sheet forming step 20 can be shortened.
[0157] The slurry 11 is dehydrated by its own weight or a relatively weak pressure. Thereafter, the pressure 19 applied to the slurry may be increased stepwise or continuously. In this process, the water in the slurry 11 flows out through the mesh sheets 12, 14. Since the initial pressure 19 applied in this process is very weak, the slurry 11 is maintained at a high viscosity, and the outflow of the cellulose fine fibers can be suppressed. On the other hand, as the dehydration progresses and the concentration of the slurry 11 increases, the fluidity decreases, and the cellulose fine fibers are less likely to flow out even if a stronger pressure 9 is applied to the slurry 11.
[0158] In this forming step 20, it is preferable to apply a pressure 19 of 2.5 kPa or less in the early stages. If a pressure exceeding 2.5 kPa is applied in the early stages, the cellulose fine fibers are likely to flow out of the slurry 11. If a mesh sheet with finer mesh size is used, the flow out of the cellulose fine fibers can be suppressed even if a pressure exceeding 2.5 kPa is applied in the early stages, but in this case, there is a risk of a decrease in the overall dewatering efficiency. The pressure in this early stage may be substantially atmospheric pressure. Alternatively, the pressure may be due only to the weight of the mesh sheet 14 itself.
[0159] After the initial pressurization has dehydrated the material to a certain extent, it is advisable to increase the pressure 19. The pressure 19 is gradually increased, and finally, the pressure is set to 50 kPa or more, preferably 100 kPa or more, and more preferably 200 kPa or more.
[0160] After the slurry 11 is pressed at a pressure of 50 kPa or more for 10 minutes or more, the mold 13 is removed to obtain a wet sheet.
[0161] (Heat and pressure process) In the heating and pressurizing step 30, the mixture is dehydrated, dried and densified under conditions of 1 to 50 MPa and 100 to 150° C. to obtain a green compact X.
[0162] The thus obtained molded body X preferably has a density of 0.8 to 1.5 g / m 3 , more preferably 0.9 to 1.4 g / m 3 , and particularly preferably 1.0 to 1.3 g / m 3 The density of the molded body X is 0.8 g / m 3 If the strength is less than 100%, the strength may be deemed insufficient due to a decrease in hydrogen bonding points.
[0163] The density of the molded body X is a value measured in accordance with JIS-P-8118:1998.
[0164] If necessary, additives such as antioxidants, corrosion inhibitors, light stabilizers, ultraviolet absorbers, heat stabilizers, dispersants, defoamers, slime control agents, and preservatives may be added to the cellulose fiber slurry S.
[0165] The wet sheet of the present invention can be used as a material for a three-dimensional molded product. EXAMPLES
[0166] Next, an embodiment of the present invention will be described. (1) First, raw pulp (LBKP, moisture content 97% by mass) and cellulose nanofibers (LBKP, moisture content 97% by mass) were mixed as cellulose fibers to prepare a slurry of cellulose fibers with a solid content concentration of LBKP cellulose nanofibers of 3% by mass. The LBKP cellulose nanofibers were obtained by pre-beating the raw pulp (moisture content 97% by mass) with a refiner and defibrating it with a high-pressure homogenizer. This LBKP cellulose nanofiber was an aqueous dispersion with a concentration of 3% by mass based on the solid content. The obtained LBKP cellulose nanofibers had an average fiber diameter of 30 nm and a crystallinity of 75%. The mixture of the LBKP cellulose nanofiber aqueous dispersion and pulp mixed with an agitator was centrifuged at 8500 rpm for 10 minutes with a centrifuge (HITACHI, refrigerated centrifuge CR22N) to obtain a concentrated mixture. The concentrated mixture had a solid content concentration of LBKP cellulose nanofibers of 5% by mass. To this concentrated mixture, an aqueous dispersion of LBKP cellulose nanofibers and dilution water were added, and the mixture was stirred and degassed in a planetary centrifugal mixer (Awatori Rentaro) at 2000 rpm for 3 minutes to obtain a slurry with a solid concentration of 5% by mass. (2) The slurry prepared in (1) above was applied onto a 300 mesh wire mesh (lower wire mesh), and then another 300 mesh wire mesh (upper wire mesh) was placed on top of the slurry to form a laminate consisting of wire mesh, slurry, and wire mesh. (3) The slurry sandwiched between the upper and lower wire meshes was pressed to obtain a wet sheet. Here, the laminate was placed on a support stand with the lower wire mesh on the bottom and the upper wire mesh on the top. A wet sheet obtained by placing a 5 kg weight on the upper wire mesh for 10 seconds was used as Test Example 1, a wet sheet obtained by placing a 5 kg weight on the upper wire mesh for 5 minutes was used as Test Example 2, and a wet sheet obtained by applying a pressure of 0.41 MPa to the upper wire mesh in the direction of the lower wire mesh for 5 minutes was used as Test Example 3. The wet sheets (Test Examples 1 to 3) were each made into test pieces measuring 10 cm in length, 10 cm in width, and 0.2 cm in thickness. (4) For each test piece of the wet sheet (Test Examples 1 to 3), both sides of the wet sheet were entirely covered with a resin film having a thickness of 0.04 mm to form a coating. This coating was placed on a support, and a pressure of 100 kPa was applied to the coating in the thickness direction for 1 second to measure the thickness. In addition, a pressure of 100 kPa was applied to the coating in the thickness direction for 5 seconds to measure the thickness, and the thickness change rate was calculated. (5) In addition, for Test Examples 1 to 3, the solids concentration (mass%) of the LBKP cellulose nanofiber was measured.
[0167] The results are shown in Table 1.
[0168] [Table 1]
[0169] (others) Unless otherwise specified, the above JIS, TAPPI and other tests and measurement methods are performed at room temperature, particularly 25°C, and at atmospheric pressure, particularly 1 atm. [Industrial Applicability]
[0170] INDUSTRIAL APPLICABILITY The present invention can be used as a cellulose fiber molded article and a method for producing the same. [Explanation of symbols]
[0171] 10 Preparation process 20 Wet sheet forming process 30 Heat and pressure process S Slurry P Pulp W Water or other medium X Molded object
Claims
1. The present invention comprises pulp and cellulose fine fibers having an average fiber diameter of 10,000 nm or less, The moisture content is 60% by mass or more, and the thickness is 0.8 mm or more and 10 mm or less. A moist sheet characterized by:
2. The cellulose fine fibers are made of at least one of cellulose nanofibers and microfibrillated cellulose having an average fiber diameter larger than that of the cellulose nanofibers. The wet sheet according to claim 1.
3. The thickness change rate calculated from the following formula 1 is 0.4 or less. The moist sheet according to claim 1 or 2. [Formula 1] Thickness change rate=((thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 1 second)−(thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 5 seconds))÷(thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 1 second)
4. The solid content concentration of the cellulose fine fibers is 10% by mass or more. The wet sheet according to any one of claims 1 to 3.
5. A heating and pressurizing step is provided in which the wet sheet is heated and pressed to obtain a molded body, The wet sheet contains pulp and cellulose fine fibers having an average fiber diameter of 10,000 nm or less, has a moisture content of 60% by mass or more, and has a thickness of 0.8 mm or more and 10 mm or less. The method for producing a molded body comprising the steps of:
6. A preparation step of mixing pulp and cellulose fine fibers having an average fiber diameter of 10,000 nm or less to prepare a slurry; a forming step of sandwiching the slurry between two opposing mesh sheets and applying pressure to dehydrate the slurry to form a wet sheet; A heating and pressurizing step is provided in which the wet sheet is heated and pressed to obtain a molded body, The wet sheet has a moisture content of 60% by mass or more and a thickness of 0.8 mm or more and 10 mm or less. The method for producing a molded body comprising the steps of:
7. The cellulose fine fibers are made of at least one of cellulose nanofibers and microfibrillated cellulose having an average fiber diameter larger than that of the cellulose nanofibers. A method for producing the molded article according to claim 5 or 6.
8. The thickness change rate calculated from the following formula 1 is 0.4 or less. The method for producing the molded article according to any one of claims 5 to 7. [Formula 1] Thickness change rate=((thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 1 second)−(thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 5 seconds))÷(thickness of wet sheet after applying a pressure of 100 kPa in the thickness direction for 1 second)
9. The solid content concentration of the cellulose fine fibers is 10% by mass or more. The method for producing the molded article according to any one of claims 5 to 8.
10. The forming step is a step carried out without substantial heating. A method for producing the molded article according to claim 6.
Citation Information
Patent Citations
Method of manufacturing wood fiberboard, and wood fiberboard
JP2012111063A
CNF formation method and CNF molded body obtained by the same method
JP2016094683A
3d moldable sheet material
JP2018534393A
Method for producing pulp molded body
JP2019183350A
Molded body of cellulose fibers and manufacturing method thereof
JP2020059962A
Cited By
Wet cellulose fiber sheet and method for producing cellulose fiber molded body
US12630980B2
Wet cellulose fiber sheet and method for producing cellulose fiber molded body
US20240003095A1